Asuhan Keperawatan pada Pasien Preoperatif Pterigium - I Made Widastra; I Made Mertha; I Made Oka Bagiarta (Jurnal Gema Keperawatan, 2014)
The aim of this study is to describe preoperative nursing care for patient with pterygium in Indera Hospital Denpasar. This study uses a descriptive research design with cross sectional approach. The method used to determine the sample is non-probability sampling is purposive sampling with a sample obtained by 45 patients. This study was conducted in May-June 2013 at Indera Hospital Denpasar. The results of this study is that the assessment of patient with pterygium in preoperative nursing care majority is Good (77.5%). At diagnosis, the majority value is Enough (60%). In the intervention, the majority value is Good (80%), as well as the implementation and evaluation of the majority value is Good (100%), and the majority value for nursing care for patient with pterygium is Good (83,5%).